Dimitrie Cantemir – on the language of the Moldovans, a translation from Latin including a commentary - Borowy, Anna (Balcanica Posnaniensia. Acta et studia, 2021)
The main aim of this paper is the Polish translation and the comment of the chapter De lingua Moldavorum, a part of the work called Descriptio Moldaviae written by Dimitrie Cantemir, voivode of Moldavia, in the early 18th century at the request of the Royal Academy in Berlin. The translation is based on the Latin text. It is the first attempt to introduce the text of Descriptio Moldaviae to Polish readers. The commentary is based on the philological methodology and contains primarily grammar and lexical remarks. The first part of the paper is a historical and cultural introduction to the topic.